Synthesis of stable α-fluoromethyl putative carbanions via a chemoselective reduction-monofluoromethylation sequence of diselenides under sustainable conditions. (9th April 2021) - Senatore, Raffaele; Malik, Monika; Urban, Ernst; Holzer, Wolfgang; Pace, Vittorio
Abstract: α-Fluoromethyl selenoethers were prepared through a sequential one-pot diselenide reduction-fluoromethylation with the fluorinated, highly manipulable C1 source ICH2 F. The reaction benefited from the employment of the environmentally friendly solvent MeTHF (2-methyltetrahydrofuran) which enabled to maximize the efficiency of both steps of the technique. A series of variously functionalized analogues – featuring a remarkable degree of stability imparted by selenium - could be chemoselectively accessed in high yield and purity through an intuitive and experimentally simple protocol. Graphical abstract: Image 1